1968
DOI: 10.1136/bmj.1.5595.801
|View full text |Cite
|
Sign up to set email alerts
|

Increased factor IX levels in puerperium during administration of diethylstilboestrol.

Abstract: Iron Absorption in Liver Disease-Brown et al. BRITIH 801The high absorption in lupoid hepatitis is interesting in that R. Williams (personal communication, 1965) has also found a high iron absorption in this condition; that this is not due to accompanying pancreatic damage is suggested by the finding that neither of these two patients showed a diminished iron absorption when the test was repeated with the addition of pancreatin. A third patient with infectious hepatitis also showed no change in absorption wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1969
1969
1989
1989

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…The average factor IX level on the first puerperal day, before initiation of treatment, was a little higher in the stilboestrol group of patients, but the variation in this group was greater than in the other two groups and the group In lactating women we found a transient rise in mean plasma factor IX levels from the already raised levels of late pregnancy on the third puerperal day only. This agrees with the results of Daniel et al (1968). We have shown that after a single 45-mg. injection of hexoestrol factor IX levels are significantly increased over those in control patients until the fourth day.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The average factor IX level on the first puerperal day, before initiation of treatment, was a little higher in the stilboestrol group of patients, but the variation in this group was greater than in the other two groups and the group In lactating women we found a transient rise in mean plasma factor IX levels from the already raised levels of late pregnancy on the third puerperal day only. This agrees with the results of Daniel et al (1968). We have shown that after a single 45-mg. injection of hexoestrol factor IX levels are significantly increased over those in control patients until the fourth day.…”
Section: Resultssupporting
confidence: 93%
“…We have shown that after a single 45-mg. injection of hexoestrol factor IX levels are significantly increased over those in control patients until the fourth day. Although the 90-mg. course of oral stilboestrol administered over a six-day period which we employed was only half the dose given by Daniel et al (1968), significantlv raised plasma factor It levels were still present until after the eighth day of the puerperium.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…There is also believed to be an increased thrombotic tendency in women whose lactation is suppressed by oestrogens (Daniel et al, 1968). Whether the action of oestrogens in haemostasis is due to an effect on blood-clotting factors, on blood platelets, or on the blood vessel wall is not certain (Ulutin, 1969).…”
Section: Discussionmentioning
confidence: 99%